Le madhisme en Turquie : L’« incident de Menemen » en 1930 - Hamit Bozarslan (Revue des Mondes Musulmans et de la Méditerranée)
Revisiting an « incident » that took place in 1930 in Turkey, this article analyzes mahdism as an object of social and political history. The « messianism of Menemen » is neither solely a consequence of the radicalisation of the Turkish religious field during thel930s, nor exclusively an expression of social contest. It is a product of the combined effect of both elements. Throughout this exceptional moment, the religious field took a much more radical shape than before. At the same time, it changed the nature of the social opposition which gave it an eschatological aspect. The combination of these two registers, the religious and social ones, explains why the legitimacy of the state was so radically rejected in Menemen and why the state responded to the messianism with a massive coercion.